Evolution of wing scales in Diptera documented by fossils - Ewa Krzemińska; Wiesław Krzemiński; Iwona Kania-Kłosok; Jadwiga Stanek-Tarkowska; Kornelia Skibińska; Daubian Santos (Zoological Letters)
Abstract Among the insects with wings clad in scales, the butterflies are the best known and those showing greatest variety of scale types. In the Diptera, some families or particular genera of two large groups are known to bear scales on wings, i.e., mosquitoes (Culicomorpha) and moth flies (Psychodomorpha). From among another large dipteran group, the crane-flies (Tipulomorpha), scales are present on wings only in one small genus, Maietta Alexander, now endemic to the southwestern coast of South America. Here, we describe an Eocene ancestor of Maietta, embedded in Baltic amber, Maietta hoffeinsetta, n. sp. This species and its recent congeners document evolution of scale cover from sparse and scarce, restricted only to anterior portion of wing, to complete and dense. A similar parallel evolutionary route was previously described in the Culicidae. The fossil representative of Maietta provides also a further example of biogeographical relationships of Baltic fauna with recent congeners distributed today far from Europe. The present finding prompts a discussion on a possible role of scales in adaptation to post Eocene cooling down of climate.